2017
DOI: 10.33844/mbr.2017.60378
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effect of perceived logistics service quality on brand factors in the e-commerce context

Abstract: In e-commerce industry while most of the transactions happen electronically, logistics activities are still required to ship products to end points. Firms that operate in e-commerce industry should consider logistics as a critical success factor if they want to be successful in operations. Studies show that customers choose strong brands in e-commerce to get better logistics service. Main purpose of this research is to examine the consequences of logistics service quality on brand factors considering e-commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…The positive relationship between the above three service quality dimensions and trust has been empirically confirmed in the literature [21]. Surucu et al [16] found that order accuracy, personal contract quality, order discrepancy handling, timeliness of order delivery, ordering procedure, and order condition positively related to consumers' trust in the brand, implying that for logistics service providers, service process quality, service outcome quality, and service recovery quality significantly impact trust. Kim et al [17] suggested that when consumers feel that the service failure has been appropriately addressed, their perception of the store's service recovery quality will be strengthened, leading to a higher trust in the store.…”
Section: The Effects Of Service Process Quality Service Outcome Quali...mentioning
confidence: 77%
“…The positive relationship between the above three service quality dimensions and trust has been empirically confirmed in the literature [21]. Surucu et al [16] found that order accuracy, personal contract quality, order discrepancy handling, timeliness of order delivery, ordering procedure, and order condition positively related to consumers' trust in the brand, implying that for logistics service providers, service process quality, service outcome quality, and service recovery quality significantly impact trust. Kim et al [17] suggested that when consumers feel that the service failure has been appropriately addressed, their perception of the store's service recovery quality will be strengthened, leading to a higher trust in the store.…”
Section: The Effects Of Service Process Quality Service Outcome Quali...mentioning
confidence: 77%